1997
DOI: 10.1046/j.1471-4159.1997.69010223.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Bcl‐2 in Adult Human Brain Regions with Special Reference to Neurodegenerative Disorders

Abstract: The expression of the protooncogene bcl‐2, an inhibitor of apoptosis in various cells, was examined in the adult human brain. Several experimental criteria were used to verify its presence; mRNA was analyzed by northern blot with parallel experiments in mouse tissues, by RNase protection, and by in situ hybridization histochemistry. Bcl‐2 protein was detected by western blot analysis and immunohistochemistry. Two bcl‐2 mRNA species were identified in the human brain. The pattern of distribution of bcl‐2 mRNA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(20 citation statements)
references
References 40 publications
0
18
1
1
Order By: Relevance
“…Engidawork et al (2001) found increased Bcl-2 by ELISA in AD cerebellum, but the cortical increase did not reach statistical significance. Vyas et al (1997) saw no changes in expression of Bcl-2 in neurons of the nucleus basalis in AD. The conclusions from these studies would argue that there is an increase in Bcl-2 expression in AD, however, this is most strongly associated with reactive glial cells near plaques, and seems more associated with membrane than cytosolic fractions.…”
Section: Discussionmentioning
confidence: 81%
“…Engidawork et al (2001) found increased Bcl-2 by ELISA in AD cerebellum, but the cortical increase did not reach statistical significance. Vyas et al (1997) saw no changes in expression of Bcl-2 in neurons of the nucleus basalis in AD. The conclusions from these studies would argue that there is an increase in Bcl-2 expression in AD, however, this is most strongly associated with reactive glial cells near plaques, and seems more associated with membrane than cytosolic fractions.…”
Section: Discussionmentioning
confidence: 81%
“…This antibody (clone 124) has been previously characterized in human and nonhuman primates using Western blot techniques, and recognizes the 26 kD band characteristic of bcl-2 protein in several tissues, including the brain (Bernier and Parent, 1998;Pezzella et al, 1990;Vyas et al, 1997). Moreover, transfection studies in monkey (vero) cells engineered to overexpress either bcl-xl or bcl-2 protein, show that the clone 124 antibody specifically stains bcl-2, but not bcl-xl, expressing cells (Bernier and Parent, 1998).…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…It is interesting that apoptotic neurons associated with neurodegenerative disorders, such as Parkinson's and Alzheimer's diseases, have altered Bcl2 expression (Vyas et al, 1997;Mattson, 2000). Actually Bcl2, in addition to its antiapoptotic functions, has shown differentiative and neurotrophic properties.…”
Section: Downloaded Frommentioning
confidence: 99%